Phase II Trial of Acai Juice Product in Biochemically Recurrent Prostate Cancer. (December 2018) - Kessler, Elizabeth R.; Su, Lih-Jen; Gao, Dexiang; Torkko, Kathleen C.; Wacker, Michael; Anduha, Mary; Chronister, Nicole; Maroni, Paul; Crawford, E. David; Flaig, Thomas W.; Glode, L. Michael; Lam, Elaine T.
Background: Plant derivatives have been studied as therapies for prostate cancer based on their purported anti-inflammatory and antioxidant properties and low toxicities. The acai berry is an example of a plant rich in phytochemicals, which may slow the growth of prostate cancer.Methods: This was a phase II, Simon 2-stage clinical trial in patients with biochemically recurrent prostate cancer with a primary endpoint of prostate-specific antigen (PSA) response. Patients were asymptomatic, with a rising PSA of at least 0.2 ng/mL, and were treated with twice daily intake of Acai Juice Product until PSA progression, with a primary endpoint of PSA response.Results: Twenty-one patients were enrolled in the first stage of the trial. One of those patients had a PSA response within the study time period. The PSA doubling time was lengthened in 71% of patients (95% confidence interval = 48% to 89%) on the trial, and in a small number of responders, this was sustained over an extended time.Conclusions: This study did not meet its primary endpoint of 50% PSA response. Nevertheless, the overall tolerability and effects on PSA stabilization warrant further exploration in a biochemically recurrent population.